Acetone adsorption to (BeO)12, (MgO)12 and (ZnO)12 nanoparticles and their graphene composites: A density functional theory (DFT) study - Mo, Y.; Li, H.; Zhou, K.; Ma, X.; Guo, Y.; Wang, Shaobin; Li, L. (Elsevier BV North-Holland, 2019)
© 2018 Elsevier B.V. Acetone, one of the most common VOCs, could cause serious air pollution and threat the human health when someone is exposed to certain concentration of acetone. Thereof, acetone detection and elimination in the air was significant to prohibit the hazard of acetone. Acetone adsorbed to (BeO)12, (MgO)12 and (ZnO)12 nanoparticles and their graphene composites was detailed studied by density functional theory. The adsorption energy of acetone to (MO)12 (M = Be, Mg, Zn) nanoparticles and their graphene composites were high, which means that all the adsorbents are eligible for acetone adsorption. The variation of band gap was utilized to describe the sensibility to acetone. It was found that the (ZnO)12 nanoparticle and its graphene composite were not sensitive to the acetone, while the (BeO)12 and (MgO)12, as well as their graphene composites, were sensitive to acetone. Among the (BeO)12-graphene and (MgO)12-graphene, the latter exhibits more sensitive than the former. The conventional transition state theory was been took to estimate the recovery time. According to our calculation, (BeO)12 and (ZnO)12 nanoparticles and all (MO)12 graphene composites have too long recovery time for the high adsorption energy hampering the recovery of the adsorbents. Contrastingly, (MgO)12 nanoparticle is sensitive to acetone and has receivable recovery time. Therefore, (BeO)12, (MgO)12 and (ZnO)12 nanoparticles and their graphene composites may be potential adsorbents for acetone adsorption for their relatively high adsorption energy. The (MgO)12 nanoparticle could be an excellent gas sensor for detecting acetone due to the sensitivity acetone and receivable recovery time.